A review of patterns of practice and clinical guidelines in the palliative radiation treatment of uncomplicated bone metastases. Issue 1 (July 2017) - Ganesh, Vithusha; Chan, Stephanie; Raman, Srinivas; Chow, Ronald; Hoskin, Peter; Lam, Henry; Wan, Bo Angela; Drost, Leah; DeAngelis, Carlo; Chow, Edward
Abstract: Background and purpose: Single fraction radiation treatment (SFRT) is recommended for its equivalence to multiple-fraction (MF) RT in the palliation of uncomplicated bone metastases (BM). However, adoption of SFRT has been slow. Materials and methods: Literature searches for studies published following 2014 were conducted using online repositories of gray literature, Ovid MEDLINE, Embase and Embase Classic, and the Cochrane Central Register of Controlled Trials databases. Results: A total of 32 articles detailing patterns of practice and clinical practice guidelines were included for final synthesis. The majority of organizations have released high level recommendations for SFRT use in treatment of uncomplicated BM, based on evidence of non-inferiority to MFRT. There are key differences between guidelines, such as varying strengths of recommendation for SFRT use over MFRT; contraindication in vertebral sites for SFRT; and risk estimation of pathologic fractures after SFRT. Differences in guidelines may be influenced by committee composition and organization mandate. Differences in patterns of practice may be influenced by individual center policies, payment modalities and consideration of patient factors such as age, prognosis, and performance status. Conclusion: Although there is some variation between groups, the majority of guidelines recommend use of SFRT and others consider it to be a reasonable alternative to MFRT.